Cyberchondria and polypharmacy in university students in Huancayo, 2024 - Calle Vilca , Mónica Alejandra (2025)
Objective: To determine cyberchondria and its relationship with polypharmacy among students of Franklin Roosevelt University in Huancayo. Material and Methods: The research is applied in nature. It follows a cross-sectional design regarding the study period and is correlational in terms of its level. The design is non-experimental. Results: The average cyberchondria score was 2.93, indicating a moderate level of cyberchondria in the studied population. Overall, each dimension also showed a moderate level. A moderate level of cyberchondria was found in 68.9% of participants, while only 4.8% exhibited a high level. Additionally, 5.2% reported using more than four medications, which is classified as polypharmacy according to WHO criteria. Among participants with a moderate level of cyberchondria, 57.1% reported engaging in polypharmacy, whereas only 7.1% of those with a high level of cyberchondria did so. Conclusions: A significant association was found between the level of cyberchondria and the number of medications used.